Direct Thrombin Inhibitor Resistance and Possible Mechanisms. Issue 11 (December 2016) - Cardinale, Maria; Ha, Michael; Liu, Michael H.; Reardon, David P.
Objective: To report 3 cases in which doses of bivalirudin higher than commonly used in clinical practice were required in order to achieve therapeutic anticoagulation as monitored by the activated partial thromboplastin time (aPTT). Case Summary: The medical records of 3 patients who required large doses of bivalirudin to remain therapeutic were thoroughly reviewed. In all 3 patients, bivalirudin was initiated at a rate appropriate for the patients' renal function and titrated using a nurse-driven protocol with recommended dose adjustments based on aPTT. Indications for bivalirudin were anticoagulation in intra-aortic balloon pump, treatment of deep vein thrombosis, and heparin-induced thrombocytopenia with thrombosis. Target aPTT was achieved between 25.5 and 134 hours after initiation despite appropriate titration intervals per protocol. Discussion: Bivalirudin is a direct thrombin inhibitor frequently used off-label for the medical management of heparin-induced thrombocytopenia. It typically exhibits predictable, dose-dependent anticoagulation. Heparin-induced thrombocytopenia was suspected in 2 of the 3 cases and confirmed in 1. In all 3 patients, target aPTT was initially achieved with doses between 0.456 and 1.0 mg/kg/h after a median of 30.7 hours; up to 1.8 mg/kg/h was required to maintain therapeutic aPTT. In 2 of the cases, the international normalized ratio also increased unexpectedly upon achievement of therapeutic aPTT values. Conclusion: Direct thrombin inhibitors may be subject to resistance mechanisms similar to those previously described in patients receiving heparin. The anticoagulation status of these patients remains unknown.